Ag+-promoted zinc oxide [Zn(O):Ag]: A novel structure for safe protection of human skin against UVA radiation. (August 2018) - Abadi, Parvaneh Ghaderi-Shekhi; Shirazi, Farshad H.; Joshaghani, Mohammad; Moghimi, Hamid R.
Abstract: Different sunscreens are employed to prevent photo damage (cancer, inflammation, etc.), including ZnO. ZnO is safe when applied as micro-size particle. To overcome some visual problems of ZnO micro-size particles, this sunscreen has been introduced as nano-size particles. Unfortunately, ZnO nanoparticles have raised some health concerns, due to Zn +2 release. On the other hand, it has been shown that ZnO metallic lattice change by metal doping decreases its solubility and toxicity. Therefore, we have decided here to develop new ZnO metallic lattice to reduce its cytotoxicity. In this study, Ag +1 -promoted Zn-based nanocompounds [Zn(O):Ag] were synthesized as a novel compound and were characterized. XRD analysis showed that Ag +1 ion percolates into ZnO crystalline lattice and changes its lattice properties (strength bond, vacancies, and etc.). Cell culture studies and MTT assay on human skin (HFF-1) cells exposed to UVA radiation showed that [Zn(O):Ag] was increased cells viability in the presence of UVA radiation compared to ZnO. Actually, Ag +1 ion has catalyzed photoactivity of ZnO compound. UV-blocking tests showed that UVA-absorbance of [Zn(O):Ag] has increased compared to ZnO. Dichlorofluoroscein diacetate-ROS assay and Zn +2 release experiments in the presence of cells showed that [Zn(O):Ag] has reduced Zn +2 ions release into culture medium and its toxicity. Our study shows that doped ZnO nanostructure has the potential to be applied as a safe and effective nanoparticulate sunscreen. Graphical abstract: Unlabelled Image Highlights: The [Zn(O):Ag] synthesizes to engineer a safe ZnO compound through metal doping. Physicochemical tests show that Ag-dopants percolate in crystalline lattice of ZnO. The [Zn(O):Ag] obtains with high stabile crystalline lattice in culture medium. At presence [Zn(O):Ag], intracellular ROS generation decreases under UVA light. The [Zn(O):Ag] is a safe protection for human skin cells against UVA light.